Como é trabalhado o ensino de artes no 4° e 5° ano do ensino fundamental na escola municipal Manoel de Sousa Lima: um estudo de caso no povoado folha grossa, zona rural de Tocantinópolis-TO - Moraes, Estefany Conceição (Universidade Federal do Tocantins, 2020)
Its main objective is to understand how the discipline of Artis worked in the 4th and 5th grade of elementary school in a multi-grade class, from the Manoel de Sousa Lima Municipal School in the Folha Grossa Village, rural area of Tocantinópolis-TO. In the specific objectives I emphasize the importance of: analyzing how the Artclasses are developed at school; observe what resources the teacher uses for the development of the Artclass; observe the challenges present in arts education in a rural school; Verify the education of the teacher who teach arts in school. I have as research problem, howis the teaching of arts in a multi-grade class, at Manoel Sousa Lima Municipal School, Folha Grossa Village, rural area of Tocantinópolis-TO. In the research I used as methodological mechanisms: field research, bibliographic research, observation at theManoel de Sousa Lima Municipal School, analysis of the didactic material, to collect data regarding the methodology used by the teacher in Art classes and case study, based on the research. qualitative. Thus, initially, the bibliographic research was carried out, aiming to make more knowledge and information enriched, presenting other authors who can help in the research on the teaching of the arts. Then I conducted the field research where I had the use of interviews with the teacher of the class of 4th and 5th grade ofthe school, who teaches the Artclasses, so the presentation of the information that was collected was presented in each way. result obtained in the field research. The results obtained in the research was that the teaching of arts is more focused on the process of creation from drawings and paintings in the classroom, where students come to develop activity put by the teacher, in order to practice these skills during Artclasses. . Educators working with multi-grade classes face major challenges as they teach their classes to two groups together in a single room and can find in this space students who have more difficulties, some have more facilities, that is, each student has his own pace. It is noticed the absence of teacher education in arts, because it is important the teacher education in arts, so that it allows a teaching learning for its students, in order to provide its development and its formation with individual, from the contact with the languages artistic.